The Effectiveness of Animated Video Learning Media in Enhancing the Physical Fitness of Elementary School Students - Bayu Purwo Adhi; Kusmiyati Kusmiyati (Universitas Riau, 2025)
Advances in data technology require Physical Education, Sports, and Health (PJOK) teachers to utilize more creative and innovative learning media to optimally support the improvement of students' physical fitness. This study aims to design and evaluate the effectiveness of animation-based video learning media on physical fitness material applied to fifth-grade students at SDN Gunung Gedangan 1 Elementary School in Mojokerto City. This study applied a Research and Development (R&D) approach involving 29 students as subjects selected using total sampling technique. Data collection was carried out through observation, questionnaire distribution, and pretest and posttest implementation. Media effectiveness testing was applied using Paired Sample t-Test analyzed using SPSS software version 23. The results of data processing indicate that the t-count value of 82.990 exceeds the t-table value of 1.6507, with a significance level of 0.001, which is less than 0.05. These findings indicate a significant difference between the pretest and posttest results. The average score of students in the pretest stage was 69.43, then increased to 79.96 in the posttest. These results reinforce the finding that the use of animation-based video media can have a positive impact on improving students' physical fitness. Thus, animated learning videos are considered feasible to be used as one of the innovative learning media in the implementation of PJOK learning at the elementary school level.